INISIATIF Culture Health Index: Mengukur Tingkat Kesehatan Budaya Organisasi BPJS Kesehatan - Syarifuddin Syarifuddin; Afrizayanti; andi afdal (BPJS Kesehatan, 2022)
Background: Organizational culture is one of the key HR management elements in BPJS Kesehatan. Optimal management of organizational culture is expected to be able to make a significant contribution to achieving organizational targets, starting from careful planning, effective and efficient program execution, and measuring the effectiveness of cultural programs as an objective evaluation mechanism. To improve the management of organizational culture that is more optimal in the future, an objective evaluation is very important to do. Purpose: This study aims to obtain an overview of the level of organizational culture health index in BPJS Kesehatan. Methods: This study uses a descriptive quantitative approach. Data collection was carried out by filling out the Organization Culture Health Index (OCHI) survey by all BPJS Kesehatan employees as respondents (the participation rate in filling out the survey was 96.79% of the population) and focus group discussions (FGD) to obtain the required qualitative information. Results and Discussion: Based on the measurement results, the level of organizational culture health in BPJS Kesehatan is generally in the